2021
DOI: 10.5811/westjem.2021.9.52016
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Depression Screen Is Associated with Emergency Medicine Resident Burnout and Is not Affected by the Implementation of a Wellness Curriculum

Abstract: Introduction: While burnout is occupation-specific, depression affects individuals comprehensively. Research on interventions for depression in emergency medicine (EM) residents is limited. Objectives: We sought to obtain longitudinal data on positive depression screens in EM residents, assess their association with burnout, and determine whether implementation of a wellness curriculum affected the rate of positive screens. Methods: In February 2017, we administered the Maslach Burnout Inventory and the Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Our rates of positive screens for depression/anxiety among emergency HCWs were within the range of that shown in previous studies during this period (anxiety [13%–44%], 6 , 9 , 10 , 12 , 21 depression [20%–50%], 5 , 6 burnout [30%–49%]). 6 , 10 , 22 , 23 Although limited and mainly measured in smaller populations, prepandemic studies have demonstrated high overall rates of burnout 24 and depression 25 among EPs, particularly among residents. Nurses also have high baseline rates of depression and burnout especially when hospital based.…”
Section: Discussionmentioning
confidence: 99%
“…Our rates of positive screens for depression/anxiety among emergency HCWs were within the range of that shown in previous studies during this period (anxiety [13%–44%], 6 , 9 , 10 , 12 , 21 depression [20%–50%], 5 , 6 burnout [30%–49%]). 6 , 10 , 22 , 23 Although limited and mainly measured in smaller populations, prepandemic studies have demonstrated high overall rates of burnout 24 and depression 25 among EPs, particularly among residents. Nurses also have high baseline rates of depression and burnout especially when hospital based.…”
Section: Discussionmentioning
confidence: 99%
“…At Months 3, 6, 9, and 12 of intern year, the prevalence of depression was 17.8%, 20.5%, 20.8%, and 18.8% respectively. Williamson et al 5 analyzed data from 382…”
Section: Discussionmentioning
confidence: 99%
“…At Months 3, 6, 9, and 12 of intern year, the prevalence of depression was 17.8%, 20.5%, 20.8%, and 18.8% respectively. Williamson et al 5 . analyzed data from 382 EM residents of all postgraduate years and found rates of positive depression screen ranging from 27.9% to 40% at various points of the year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations